Persepsi Mahasiswa Generasi Z Terhadap Sejarah - Butet Nurpadilah Lubis; Ilma Nur Firdaus; Malena Sari Franlin; Nur Asiah (CV Putra Publisher, 2023)
History is a branch of science that examines systematically the entire development process of change or the dynamics of people's lives with all aspects of their life in the past. History is a crucial aspect of living life, especially for the Z generation. Generation Z is also known as the regeneration, which means the generation that uses the internet as one of the main needs for their lives. This indirectly triggers the ease with which outside cultural influences influence this generation. There the researchers researched Generation Z, especially Indonesian University of Education students at the undergraduate level, as one of the universities currently dominated by Generation Z. The method used in this study used a qualitative method with a descriptive approach. Through this research the results were obtained in the form of 1) Respondents' knowledge of understanding history 86.7%, 2) Opinions regarding the importance of history 96.3%, 3) Regarding interest in knowing unknown history 83.3%, 4) regarding views that history is helpful for everyday life 63.3%, 5) Regarding the ability to be able to argue about history 50% 6) History is crucial to learn today 86.7%. Keywords: Perception, Generation Z, History